Modern Dietary Fat Intakes in Disease Promotion - De Meester, Fabien; Zibadi, Sherma; Watson, Ronald Ross (Nutrition and Health,, 2010)
The industrial and agricultural revolutions have dramatically changed our lifestyles including where we get foods and what we eat. Modern diets have moved away from a close association with historically beneficial foods and diets towards foods and diets with increased fats and contaminants and with much lower intakes of fruits and vegetables. Modern Dietary Fat Intakes in Disease Promotion focuses on the scientific evidence that defines such risks in modern diets with the consequences of increased illness, cancer and disease. There is also an emphasis on methods to reverse negative components of modern diets for health improvement. The volume is divided into five sections including the section on the behavioral aspects of eating; a second section on dietary fats; the third section examines the clinical relevance of fats and cardiovascular disease. The fourth section contains novel chapters on the potential for contaminants in fats and oils to increase risk of illnesses. The fifth section looks at dietary and pharmaceutical approaches to modify fat-induced disease and ill-health. Each section contains chapters that address treatment options as well as prevention strategies. Modern Dietary Fat Intake in Disease Promotion, edited by Fabien DeMeester, Sherma Zibadi, and Ronald Ross Watson, provides health professionals in many areas of research and practice with the most up-to-date, well-referenced, and easy-to-understand volume on the importance of identifying and treating as well as providing strategies to prevent the development of chronic, serious metabolic diseases.